Avaliação das condições da iluminação natural em salas típicas de edifícios de escritórios em Maceió-AL - Cardoso, Sara de Oliveira (2006)
Maceió, the capital of a North-eastern state in Brazil, has abundant sun and sky light during the whole year. Despite this natural resource the electrical lighting system works in full-scale throughout the day in many Office buildings. The main objective of this study is to evaluate the performance of the natural light in typical office buildings of the city, in order to suggest and recommend guidelines for future constructions, taking into account the rationalization of artificial lighting use. The study was based on a previous diagnosis of the actual conditions of different office buildings in Maceió, and was developed through computer simulations of standard office buildings. The investigation was divided in three stages: the first was an assessment of the conditions of sun lighting in the office rooms in a typical luminous day of each of the four seasons, considering the buildings’ four most recurrent directional references. In the second stage, light shelves were added to the openings of the largest rooms in reference to the four directions. Lastly, it was added a high continuous window turned to the side corridor of the building’s largest rooms in two directions. The insertion of constructive elements in the last two stages of the simulation aimed at investigating the influence of the performed changes in the improvement of the lighting uniformity in the office rooms. As a result of the first stage of the simulation, it was verified an average of 75% of variation in the illuminance between the nearest and the most distant points from the opening for the largest rooms; the addition of light shelves caused this rate to decrease to an average of 70% in the rooms with the same dimensions and of 65% with the addition of a continuous high window. The addition of the two proposed interventions (light shelves and continuous opening turned to the corridor) caused the variation between points to decrease to 50%. Therefore, the results obtained through computer simulations show that the changes suggested have significantly improved the lighting uniformity of the ambiance.